Frequency and prognostic impact of PAX5 p.P80R in pediatric acute lymphoblastic leukemia patients treated on an AIEOP‐BFM acute lymphoblastic leukemia protocol. Issue 11 (7th July 2020) - Jung, Mareike; Schieck, Maximilian; Hofmann, Winfried; Tauscher, Marcel; Lentes, Jana; Bergmann, Anke; Stelter, Marie; Möricke, Anja; Alten, Julia; Schlegelberger, Brigitte; Schrappe, Martin; Zimmermann, Martin; et al.
Abstract: PAX5 is a member of the paired box (PAX) family of transcription factors involved in B‐cell development. PAX5 P80R has recently been described as a distinct genetic B‐cell precursor (BCP) acute lymphoblastic leukemia (ALL) subtype with a favorable prognosis in adults. In contrast, an unfavorable outcome has been observed in children. Our aim was to determine the frequency of PAX5 P80R in childhood BCP‐ALL treated according to the Associazione Italiana Ematologia ed Oncologia Pediatrica‐Berlin‐Frankfurt‐Muenster (AIEOP‐BFM) ALL 2000 protocol and to evaluate its clinical significance within this study cohort. The analyses included 1237 patients with ALL treated in the AIEOP‐BFM ALL 2000 trial with complete information for copy number variations (CNVs) of IKZF1, PAX5, ETV6, RB1, BTG1, EBF1, CDKN2A, CDKN2B, and ERG . A customized TaqMan genotyping assay was used to screen for PAX5 P80R . Sanger sequencing was used to confirm PAX5 P80R ‐positive results as well as to screen for second variants in PAX5 . Agilent CGH + SNP arrays (e‐Array design 85 320; Agilent Technologies) were performed in PAX5 P80R ‐positive patients to verify additional CNVs. Almost 2% (20/1028) of our BCP‐ALL cohort were PAX5 P80R ‐positive. White blood cell counts higher than 50 000/μl as well as male sex were significantly ( P < .05) associated with PAX5 P80R . Most of the PAX5 P80R ‐positive cases were 10 years of age or older. PAX5 P80R ‐positive samples were enriched for deletions affecting PAX5, IKZF1, CDKN2A, and CDKN2B . Compared to PAX5 P80R ‐ wildtype BCP‐ALL, PAX5 P80R ‐positive patients showed a significantly reduced 5‐year overall survival ( P = .042). Further studies should evaluate the interaction of PAX5 P80R with other genetic aberrations to further stratify intermediate risk pediatric BCP‐ALL.